Resilient Image Feature Description through Evolution - BOSTANCI, Erkan (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Feature description is an important stage in many different vision algorithms. Image features detected by various detectors can be described using descriptors either with a binary or floating-point structure. This study presents the use of evolutionary algorithms, namely Genetic Algorithms (GA), in order to improve the robustness of the feature descriptors against increasing levels of photographic distortions such as noise or JPEG compression. Original feature descriptors were evolved in order to reduce the descriptor distance for the mentioned test cases. Results, tested using a statistical framework, suggest that the evolved descriptors offer better matching performance for two state-of-the-art descriptors.